Study on surface hydrogenated Ti6Al4V alloy for orthopedic implants - Yu-Chien Lin; Chih-Chien Hu; Thu-Trang Nguyen; Udesh Dhawan; Ching-Yi Chou; Yueh-Lien Lee; Hung-Wei Yen; Yi-Jie Kuo; Ren-Jei Chung (Journal of Materials Research and Technology, 2024)
Titanium-based alloys exhibit superior resistance to corrosion and biocompatibility in comparison to other alloys utilized for implant applications, such as stainless steel and cobalt-based alloys. Nonetheless, no completely inert metal is suitable for implantation in the human body, as aseptic loosening of the implant or the release of ions in the vicinity of the implant can result in inflammation and implant failure. Therefore, the primary objective of this study was to employ hydrogenated titanium 6-aluminum-4-vanadium (H–Ti6Al4V) alloy to reduce reactive oxygen species (ROS) and thereby achieve the function of regulating inflammatory signaling when employed as an implant.The Ti6Al4V alloy was successfully hydrogenated using a cathodic hydrogen-charging method. The H–Ti6Al4V alloy displayed a surface Young's modulus 33.97 ± 9.21 GPa similar to that of trabecular bone (∼22.3 GPa) and notably lower hardness (3.32 ± 0.62 GPa) than the Ti6Al4V alloy (21.79 ± 2.42 GPa). In vitro and in vivo investigations indicated that the H–Ti6Al4V alloy did not negatively affect bone-related cells and triggered minimal inflammatory responses in Sprague–Dawley rats. Moreover, reduced ROS production was observed around the H–Ti6Al4V alloys, confirming that hydrogenation could effectively counteract the ROS generated during cell metabolism and indirectly impede the inflammatory response around the prosthesis, thereby rendering it a promising metallic implant for the treatment of bone defects.